Intercostal vessel screening prior to pleural interventions by the respiratory physician: a prospective study of real world practice - Bedawi, EO; Talwar, A; Hassan, M; McCracken, DJ; Asciak, R; Mercer, RM; Kanellakis, NI; Gleeson, FV; Hallifax, RJ; Wrightson, JM; Rahman, NM (European Respiratory Society, 2020)
Introduction The rising incidence of pleural disease is seeing an international growth of pleural services, with physicians performing an ever-increasing volume of pleural interventions. These are frequently conducted at sites without immediate access to thoracic surgery or interventional radiology and serious complications such as pleural bleeding are likely to be under-reported.